Zimbabwe’s community radio ‘initiatives’: Promoting alternative media in a restrictive legislative environment - Nhamo Mhiripiri (Intellect, 2023)
Unlike most nations in southern Africa, Zimbabwe has not seen the expansion in community radio stations that has been characteristic of the region from the 1990s. A number of community radio initiatives (CRIs) were formed after the 2001 Zimbabwean Broadcasting Services Act (BSA), but no licences were ever issued in any broadcasting sector. This article argues that CRIs reflected the wider political crises of the years since 2000. Even after the Global Political Agreement of 15 September 2008, no community radio station has been licensed. Taking two case studies of such initiatives - Community Radio Harare and Radio Dialogue of Bulawayo - the article investigates how they have survived the Zimbabwean political crisis. It examines the way they lobbied for the right to broadcast and how they produced and distributed programming, and utilized so-called 'roadshows' in an environment where alternative radio stations are viewed with suspicion by ZANU PF.